2019
DOI: 10.29239/j.agrikan.12.2.317-321
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution and Length-Weight Relationship of Red Snapper (<i>Lutjanus malabaricus</i>) in Pinrang Waters Regency of Pinrang

Abstract: Fisheries activities red snapper in Pinrang waters is considered to be a small scale and caught with that variety of types instrument catch fish (multi gears) one of them is bubu fishing gear. Now, the level of the utilization of red snapper is believed to have been experience symptoms of over fishing due to the high pressure in the area. The study aims to analyze the size structure and length-weight correlation of red snapper (Lutjanus sp). The study was conducted during 5 months of period, starting from Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…It was found that the stock of Malabar blood snapper in Nghe An and Ha Tinh provinces is in a sex-balanced condition (i.e. the amount of males is equal to the amount of females) during the whole year, which is in agreement with observations performed in Pinrang waters (Rapi et al ., 2020). Even though a statistically significant prevalence of males was observed in June, we tend to assume that it was an artefact of sampling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that the stock of Malabar blood snapper in Nghe An and Ha Tinh provinces is in a sex-balanced condition (i.e. the amount of males is equal to the amount of females) during the whole year, which is in agreement with observations performed in Pinrang waters (Rapi et al ., 2020). Even though a statistically significant prevalence of males was observed in June, we tend to assume that it was an artefact of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Such a sex ratio is not typical for snapper stocks; usually, they are characterized by a clear predomination of one sex (Shimose and Tachihara, 2005; Fry et al ., 2009). Although these findings also could be due to sampling artefacts, because in cases when the sample size exceeded 100 individuals and specialized fishing gear was used, the sex ratio of L. malabaricus was close to 1:1 (Fry et al ., 2009; Rapi et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers claimed that "at geographically dispersed at latitudes of more than five degrees, there will be differences in size and age when fish reaches first gonad maturity level. In addition, the difference in size also occurs due to differences in ecological conditions of the waters" (Rapi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%